Biotechnology and the human good - Mitchell, C. Ben (Book collections on Project MUSE., 2007)
Some of humankind's greatest tools have been forged in the research laboratory. Who could argue that medical advances like antibiotics, blood transfusions, and pacemakers have not improved the quality of people's lives? But with each new technological breakthrough there comes an array of consequences, at once predicted and unpredictable, beneficial and hazardous. Outcry over recent developments in the reproductive and genetic sciences has revealed deep fissures in society's perception of biotechnical progress. Many are concerned that reckless technological development, driven by consumerist impulses and greedy entrepreneurialism, has the potential to radically shift the human condition--and not for the greater good. Biotechnology and the Human Good builds a case for a stewardship deeply rooted in Judeo-Christian theism to responsibly interpret and assess new technologies in a way that answers this concern.